2007
DOI: 10.1159/000105131
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Cancer Presented with Leptomeningeal Carcinomatosis Effectively Treated with Sorafenib

Abstract: Sorafenib has been approved in the U.S. and the European Union for patients with advanced renal cell cancer (RCC). There is evidence that treatment with sorafenib can achieve partial remissions in patients with brain metastases of RCC. Case Report: We report of a patient with leptomeningeal carcinomatosis of RCC, who 10 days after initiation of sorafenib therapy showed a noticeable decrease in contrast enhancement of the tumor in a magnetic resonance imaging (MRI) scan of the brain. This partial response was v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…Interactions of sorafenib with P-gp or ABCG2 are thus far not reported. However, a few case reports indicated that sorafenib can achieve partial remission in renal cell carcinoma patients with brain metastases (8,9). Although brain metastases may contain leaky blood vessels due to neovascularization, they are often protected from adequate chemotherapy because they are still mostly behind an intact blood-brain barrier (BBB; reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions of sorafenib with P-gp or ABCG2 are thus far not reported. However, a few case reports indicated that sorafenib can achieve partial remission in renal cell carcinoma patients with brain metastases (8,9). Although brain metastases may contain leaky blood vessels due to neovascularization, they are often protected from adequate chemotherapy because they are still mostly behind an intact blood-brain barrier (BBB; reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%
“…NM from renal cell carcinoma is a rare event, with only few cases reported to date [2,3]. In the present patient, it was preceded by brain metastases, initially a single cerebellar lesion, which was surgically removed.…”
Section: Discussionmentioning
confidence: 63%
“…Some patients might even present with leptomeningeal carcinomatosis or so called neoplastic meningitis (NM). Only few cases of NM from renal cell carcinoma treated with contemporary systemic approaches have been reported [2,3]. Therefore, the present case illustrates important aspects around potential treatment options.…”
Section: Introductionmentioning
confidence: 83%
“…Por otra parte, recientemente están apareciendo en la literatura casos de regresiones rápidas de focos metastáticos en el sistema nervioso central tras la administración de sunitinib y sorafenib 39,40 .…”
Section: Metástasis Cerebralesunclassified